Reminiscing the lesson study journey in Brunei - Khalid, Madihah (The Sultan Hassanal Bolkiah Institute of Education, 2016)
This paper presents a reminiscence of the Lesson Study through the eyes and perspective of the author and is narrated in three main stages - the past, the present and the future. It initially relates how Lesson Study started in Brunei. It then relates how it began to be accepted by the teachers due to strong support from the Brunei Ministry of Education (how it grew from being practiced in one school to all primary schools now). It also stresses the importance of teachers' commitment, and finally, conveys the aspirations of the author for more widespread and successful practice of the Lesson Study in Brunei, in the future.